Protein-dependent membrane interaction of a partially disordered protein complex with oleic acid : Implications for cancer lipidomics - Chaudhuri, Arunima; Prasanna, Xavier; Agiru, Priyanka; Chakraborty, Hirak; Rydstrom, Anna; Ho, James C. S.; Svanborg, Catharina; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
Bovine α-lactalbumin (BLA) forms cytotoxic complexes with oleic acid (OA) that perturbs tumor cell membranes, but molecular determinants of these membrane-interactions remain poorly understood. Here, we aim to obtain molecular insights into the interaction of BLA/BLA-OA complex with model membranes. We characterized the folding state of BLA-OA complex using tryptophan fluorescence and resolved residue-specific interactions of BLA with OA using molecular dynamics simulation. We integrated membrane-binding data using a voltage-sensitive probe and molecular dynamics (MD) to demonstrate the preferential interaction of the BLA-OA complex with negatively charged membranes. We identified amino acid residues of BLA and BLA-OA complex as determinants of these membrane interactions using MD, functionally corroborated by uptake of the corresponding α-LA peptides across tumor cell membranes. The results suggest that the α-LA component of these cytotoxic complexes confers specificity for tumor cell membranes through protein interactions that are maintained even in the lipid complex, in the presence of OA.

Preface to special issue on protein-mediated membrane remodeling - Chakraborty, Hirak; Sengupta, Durba (Journal of Membrane Biology, 2022)

Anomalous membrane organization by omega-6 and omega-9 fatty acids - Porte, Sudha; Pandia, Swaratmika; Joardar, Ankita; Saraf, Deepashri; Pinjari, Aadil; Chakraborty, Hirak; Sengupta, Durba (Physical Chemistry Chemical Physics, 2025)
Omega fatty acids are currently being marketed as healthy food supplements as they have been implicated in multiple pathophysiological conditions, such as reducing plaque formation of A beta peptide and inhibiting SARS-CoV-2 infection. Their mode of action has been hypothesized to be via membrane reorganization by the unsaturated acyl chains, leading to the modulation of lipid-protein cross-talk. However, the lack of molecular details led us to evaluate the molecular effect of omega-6 (linolenic acid) and omega-9 (oleic acid) fatty acids on membrane organization using a consolidated approach of fluorescence spectroscopy and all-atom molecular dynamics simulation. Our results show that the effect of these omega fatty acids is sensitive to their protonation states. Contrary to the accepted notion that chain unsaturation causes membrane disordering, both experimental and simulation results demonstrate that protonated linoleic acid promotes membrane ordering, despite having two unsaturations at the fatty acyl chain. However, protonated oleic fatty acid, with reduced unsaturation, disordered the acyl chain area of the lipid membranes. Equally surprisingly, deprotonated oleic acid orders, whereas deprotonated linoleic acid disorders, the membrane core region. Interestingly, while the lipid order parameter measurements from simulations did not capture these subtle differences, the calculated rotational autocorrelation function of a membrane dye was in line with experimentally measured apparent rotational correlation times. Our work provides a comprehensive revised molecular picture of the effect of omega fatty acids on membranes and highlights the importance of rigorous comparative approaches, as experimental and simulation studies in isolation can sometimes lead to inconsistent results.